Demokrasi dan Masyarakat Madani - Budi Juliardi (Bakaba : Jurnal Sejarah, Kebudayaan dan Kependidikan, 2022)
Democracy and civil society are two concepts that cannot be separated from one another. In essence, democracy will only be implemented well in a civil society. Correspondingly, a civil society will definitely implement the principles of democracy. Today, all countries in the world claim that they apply the concept of democracy. However, is the implementation of democracy carried out in accordance with democratic principles that should be adhered to by civil society? Not necessarily, because many countries claim to adhere to the principle of democracy, but its implementation is still not democratic.